Cost analysis of improving emergency care for aged care residents under a Hospital in the Nursing Home program in Australia - Fan, Lijun (PLoS One, 2018)
BACKGROUND: This study aims to examine the costs associated with a Hospital in the Nursing Home (HiNH) program in Queensland Australia directed at patients from residential aged care facilities (RACFs) with emergency care needs. METHODS: A cost analysis was undertaken comparing the costs under the HiNH program and the current practice, in parallel with a pre-post controlled study design. The study was conducted in two Queensland public hospitals: the Royal Brisbane and Women’s Hospital (intervention hospital) and the Logan Hospital (control hospital). Main outcome measures were the associated incremental costs or savings concerning the HiNH program provision and the acute hospital care utilisation over one year after intervention. RESULTS: The initial deterministic analysis calculated the total induced mean costs associated with providing the HiNH program over one year as AU$488,116, and the total induced savings relating to acute hospital care service utilisation of AU$8,659,788. The total net costs to the health service providers were thus calculated at -AU$8,171,671 per annum. Results from the probabilistic sensitivity analysis (based on 10,000 simulations) showed the mean and median annual net costs associated with the HiNH program implementation were -AU$8,444,512 and–AU$8,202,676, and a standard deviation of 2,955,346. There was 95% certainty that the values of net costs would fall within the range from -AU$15,018,055 to -AU$3,358,820. CONCLUSIONS: The costs relating to implementing the HiNH program appear to be much less than the savings in terms of associated decreases in acute hospital service utilisation. The HiNH service model is likely to have the cost-saving potential while improving the emergency care provision for RACF residents.